Assessment of Craniofacial Complex and Hyoid Bone of Syrian Adults with Type II, Division 1 Malocclusion and Different Patterns of Vertical Growth using Cone Beam Computed Tomography (CBCT) (Journal of Hama University, 2024)
The cranial base plays a pivotal role in directing the craniofacial growth pattern; topographically and functionally, which in turn contributes to different growth patterns that may affect the location of the hyoid bone. In addition, it has been indicated that there may be an effect of race on the shape of the craniofacial structures and the face shape in the vertical direction. Therefore, the objective of this study was to describe the cranial base and the hyoid bone in Syrian adults with class II Division1 malocclusion with different Patterns of Vertical Growth using CBCT.The sample included 30 adults with Class II Division 1(11 males - 19 females). They are divided into 3 groups according to the sum of Bjork angles (Horizontal, Normal, Vertical growth pattern). A CBCT image was taken for each patient and the linear and angular measurements were performed using CS 3d imaging software. The results were analyzed using the Kruskal-Wallis test to compare between vertical facial groups and find out the significance of differences at significance level (P
Keywords: Class II Division 1, Vertical growth pattern, CBCT, Cranial Base, Hyoid bone